Study on the replacement of the hydrated lime by kaolinitic clay in mortars. (3rd October 2019) - Marvila, M. T.; Alexandre, J.; Azevedo, A. R. G.; Zanelato, E. B.; Xavier, G. C.; Monteiro, S. N.
ABSTRACT: Mortars are cement-based materials used mainly to coat and settle construction blocks. In addition to cement, their composition usually includes hydrated lime, sand, and water. The hydrated lime is important to improve the mortar workability. However, lime has a high commercial cost, and its production causes emission of CO2, a major responsible for global warming. Therefore, the purpose of this work was to investigate the possibility of total or partial replacement of hydrated lime in mortars by a kaolinitic clay with ideal plasticity parameters. Clay amounts of 0, 25, 50, 75, and 100 wt-% were used as replacement of hydrated lime in mortars. The results showed that with up to 50 wt-% of hydrated lime replacement, it is perfectly feasible to fulfil with technological parameters of standards.